2018
DOI: 10.3389/fgene.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Atlas of E3 Ubiquitin Ligase Mutations in Neurological Disorders

Abstract: Protein ubiquitination is a posttranslational modification that plays an integral part in mediating diverse cellular functions. The process of protein ubiquitination requires an enzymatic cascade that consists of a ubiquitin activating enzyme (E1), ubiquitin conjugating enzyme (E2) and an E3 ubiquitin ligase (E3). There are an estimated 600–700 E3 ligase genes representing ~5% of the human genome. Not surprisingly, mutations in E3 ligase genes have been observed in multiple neurological conditions. We construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 166 publications
(220 reference statements)
0
102
0
Order By: Relevance
“…Mutations on E3 ligases have been associated with a number of diseases, including neurological disorders (George et al, 2018;Osinalde et al, 2019). Thus, understanding their mechanism of action, as well as identifying which substrates are regulated by each E3 at different developmental stages and cell types, will provide invaluable knowledge that might contribute to develop therapeutic strategies to treat these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations on E3 ligases have been associated with a number of diseases, including neurological disorders (George et al, 2018;Osinalde et al, 2019). Thus, understanding their mechanism of action, as well as identifying which substrates are regulated by each E3 at different developmental stages and cell types, will provide invaluable knowledge that might contribute to develop therapeutic strategies to treat these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination has recently been recognized as a biological process of interest in the field of ID because some authors have reported its implication in neurological disorders that include neurodegenerative and neurodevelopmental disorders . Ubiquitination is a post‐translational modification that involves the addition of a small polypeptide called ubiquitin to target proteins.…”
Section: Molecular and Cellular Pathways Involved In Idmentioning
confidence: 99%
“…HUWE1 (OMIM *300697) encodes a HECT type E3 ligase and it is known to regulate neural differentiation and proliferation through poly‐ubiquitination of specific target proteins like MYCN, p53 and CDC6 for subsequent proteasomal degradation . HUWE1 is known to be critical in development, because its loss leads to embryonic lethality in mice .…”
Section: Molecular and Cellular Pathways Involved In Idmentioning
confidence: 99%
“…The E1 enzyme UBA1 is implicated in the aetiology of X-linked infantile spinal muscular atrophy (XL-SMA) [83], and mutations in the E2 enzyme UBE2A result in UBE2A deficiency syndrome [84], whereas the E2 enzyme UBE2K, which can catalyse protein ubiquitination independent of E3 ligases, is a pivotal factor modulating the neurotoxicity of expanded huntingtin in Huntington's disease [85]. Additionally, more than 10 distinct RNDs are also known to be originated as a consequence of defective HECT-type E3 ligases [82,101]. The vast majority of RNDs caused by E3s are due to mutations either reducing or disrupting the activity of the ubiquitin ligases, therefore resulting in impaired ubiquitination of their substrates.…”
Section: Protein Folding and Aggregationmentioning
confidence: 99%
“…The U-box domain containing E3 ligase CHIP can cause SCAR16 [103] and is also involved in Gordon Holmes syndrome, a rare neurodegenerative disorder characterized by hypogonadism and ataxia [82]. This disease can also be caused by the combination of mutations in the RING-finger type E3 ligase RNF216 [88] and consequently, astrocytes suffer many molecular changes, including proteasome inhibition [75].…”
Section: Protein Degradationmentioning
confidence: 99%